A pathogenic trace of Tannerella forsythia – shedding of soluble fully active tumor necrosis factor α from the macrophage surface by karilysin. (3rd October 2014) - Bryzek, D.; Ksiazek, M.; Bielecka, E.; Karim, A.Y.; Potempa, B.; Staniec, D.; Koziel, J.; Potempa, J.
Summary Tannerella forsythia is implicated as a pathogen causing chronic and aggressive periodontitis. However, its virulence factors, including numerous putative proteases, are mostly uncharacterized. Karilysin is a newly described matrix metalloprotease‐like enzyme of T. forsythia. Since pathogen‐derived proteases may affect the host defense system via modulation of the cytokine network, the aim of this study was to determine the influence of karilysin on tumor necrosis factor‐α (TNF‐α). The results showed that karilysin cleaved the membrane form of TNF‐α on the surface of macrophages, and that this led to an increased concentration of soluble TNF‐α in the conditioned medium. Importantly, despite partial degradation of soluble TNF‐α by karilysin, the released cytokine retained its biological activity, inducing apoptosis and stimulating autocrine pathway of pro‐inflammatory gene expression. Notably, the observed effect required proteolytic activity by karilysin, since a catalytically inactive mutant of the enzyme did not affect TNF‐α secretion. The shedding was independent of the activity of ADAM17, a major endogenous TNF‐α converting enzyme. Karilysin‐dependent TNF‐α release from the cell surface is likely to occur in vivo because human plasma, the main constituent of gingival crevicular fluid, only slightly affected the sheddase activity of karilysin. Taken together, these results indicate that karilysin modulates the host immune response through regulation of TNF‐α secretion, and should therefore be considered as a new virulence factor of T. forsythia.